The MRZ reaction helps to distinguish rheumatologic disorders with central nervous involvement from multiple sclerosis - Tilman Hottenrott (BMC Neurology, 2018)
Abstract Background Some rheumatologic disorders may initially manifest with central nervous system (CNS) affection, mimicking the clinical, magnetic resonance imaging, and cerebrospinal fluid findings of multiple sclerosis (MS). The MRZ reaction (MRZR), composed of the three respective antibody indices (AIs) against measles, rubella, and varicella zoster virus, has been found positive frequently in MS patients. However, it is unclear whether the MRZR is helpful to distinguish rheumatologic disorders with CNS involvement (RDwCNS) from MS. Methods The MRZR was evaluated in patients with RDwCNS (n = 23), MS (n = 46; age and sex matched to patients with RDwCNS), and other inflammatory autoimmune neurological diseases affecting the CNS (OIND; n = 48). Both the stringency levels that have been used in previous MRZR studies, MRZR-1 (≥ 1 of 3 AIs positive) and MRZR-2 (≥ 2 of 3 AIs positive), were applied. Results There was no statistically significant difference in the prevalence of positive MRZR between patients with RDwCNS (MRZR-1: 13.0% and MRZR-2: 8.7%, respectively) and OIND (MRZR-1: 22.9% and MRZR-2: 8.3%, respectively). Compared to these two study cohorts, the MS group exhibited significantly higher prevalences of positive MRZR (MRZR-1: 82.6%, MRZR-2: 63.0%; p < 0.005 each). Conclusions Considering the high specificity of MRZR-2 for MS found in this study, MRZR-2 can be a useful diagnostic tool for distinguishing MS from RDwCNS or OIND.